Biodiversity - functioning studies in grasslands: their design, analysis and the importance of realized diversity. - Rychtecká, Terezie (Jihočeská univerzita, 2014)
In this thesis, relationships between two facets of biodiversity, the sown species diversity and realized species diversity, and biomass production were studied using both theoretical approach and experimental data analysis. A pot biodiversity - functioning experiment was conducted to reveal the effect of initial sowing density on biodiversity effects. A comparison between several methods for biodiversity - functioning experiments analysis was made and methods requirements, results and ecological interpretations implied by their results discussed.
Biodiversity - functioning studies in grasslands: their design, analysis and the importance of realized diversity.